Law Enforcement Strategies Against Crypto-Asset Money Laundering: Challenges in Evidence and Cross-Border Cooperation - Dwi Saleha; Munawir Munawir; Djuhrijjani Djuhrijjani; Nizla Rohaya; Muhammad Nazir (Westscience Press, 2026)
This study examines law enforcement strategies in addressing cryptocurrency-based money laundering, with particular emphasis on evidentiary challenges and cross-border cooperation using a normative legal approach. The rapid development of digital assets such as Bitcoin has introduced new complexities in financial crime, enabling illicit actors to exploit decentralized systems and pseudonymous transactions. Through doctrinal analysis of legal frameworks, regulations, and international standards, including those established by the Financial Action Task Force, this research identifies key gaps in the current legal system. The findings reveal that the collection and admissibility of digital evidence remain significant obstacles due to difficulties in linking blockchain transactions to identifiable individuals, as well as limitations in technical capacity and legal procedures. Additionally, cross-border cooperation is hindered by regulatory fragmentation, jurisdictional differences, and slow mutual legal assistance mechanisms. Existing law enforcement strategies—while incorporating regulatory, technological, and institutional approaches are often insufficient and lack integration. This study concludes that strengthening international legal harmonization, enhancing digital forensic capabilities, and reforming cross-border cooperation mechanisms are essential to improving enforcement effectiveness. Furthermore, adaptive legal frameworks are needed to balance innovation in cryptocurrency with accountability and oversight. This research contributes to the development of more responsive legal strategies to combat cryptocurrency-based money laundering in an increasingly globalized digital economy.